Inovasi Pemberdayaan Generasi Z: Peran Guru BK dalam Peningkatan Kemampuan Komunikasi Interpersonal Siswa - Yacob, Fakhri (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2025)
This article examines the role of school counselors in improving students’ interpersonal communication skills through Generation Z empowerment innovation. The study was conducted at SMA Negeri 8 Banda Aceh using a mixed methods approach with a convergent parallel design. Qualitative data were collected through observations of school counselor activities and interviews with the school counselor and principal, while quantitative data were obtained through an interpersonal communication skills questionnaire administered to 10 students. The instruments consisted of the School Counselor Activity Observation Sheet (LOAGBK), School Counselor Interview Guidelines (PWGBK), Principal Interview Guidelines (PWKS), and the Students’ Interpersonal Communication Skills Questionnaire (KKKIS). The findings show that school counselor activities in strengthening students’ interpersonal communication were in the very good category, with an observation score of 87.5%. The school counselor implemented communicative and interactive services through group guidance, individual counseling, communication simulations, small-group discussions, and the use of digital media, including Google Form, WhatsApp groups, educational videos, and interactive presentations. The questionnaire results showed that students’ interpersonal communication skills reached 81%, which falls into the very high category. The strongest aspects were polite language use and group cooperation. However, students’ confidence in expressing opinions in class, ability to resolve conflicts through communication, and tendency to communicate more comfortably through social media still require further strengthening. The study suggests that school counseling services can support students’ interpersonal communication development when implemented through structured, reflective, and balanced approaches between digital media use and face-to-face communication practice. Abstrak Artikel ini mengkaji peran guru BK dalam meningkatkan kemampuan komunikasi interpersonal siswa melalui inovasi pemberdayaan Generasi Z. Penelitian dilakukan di SMA Negeri 8 Banda Aceh dengan menggunakan pendekatan mixed methods bertipe convergent parallel design. Data kualitatif diperoleh melalui observasi aktivitas guru BK dan wawancara dengan guru BK serta kepala sekolah, sedangkan data kuantitatif diperoleh melalui kuesioner kemampuan komunikasi interpersonal yang diberikan kepada 10 siswa. Instrumen penelitian terdiri atas Lembar Observasi Aktivitas Guru BK (LOAGBK), Pedoman Wawancara Guru BK (PWGBK), Pedoman Wawancara Kepala Sekolah (PWKS), dan Kuesioner Kemampuan Komunikasi Interpersonal Siswa (KKKIS). Hasil penelitian menunjukkan bahwa aktivitas guru BK dalam penguatan komunikasi interpersonal siswa berada pada kategori sangat baik dengan capaian observasi sebesar 87,5%. Guru BK melaksanakan layanan yang komunikatif dan interaktif melalui bimbingan kelompok, konseling individual, simulasi komunikasi, diskusi kelompok kecil, serta pemanfaatan media digital seperti Google Form, grup WhatsApp, video edukasi, dan media presentasi interaktif. Hasil kuesioner menunjukkan bahwa kemampuan komunikasi interpersonal siswa mencapai 81% dan berada pada kategori sangat tinggi. Aspek yang paling kuat tampak pada penggunaan bahasa yang santun dan kemampuan bekerja sama dalam kelompok. Namun, keberanian siswa dalam menyampaikan pendapat di kelas, kemampuan menyelesaikan konflik melalui komunikasi, dan kecenderungan sebagian siswa lebih nyaman berkomunikasi melalui media sosial masih perlu diperkuat. Kajian ini menunjukkan bahwa layanan BK dapat mendukung pengembangan komunikasi interpersonal siswa apabila dilaksanakan secara terstruktur, reflektif, serta seimbang antara pemanfaatan media digital dan latihan komunikasi tatap muka.